Pengembangan E-Modul Biologi Berbasis Pendekatan Saintifik pada Materi Keanekaragaman Hayati untuk Peserta Didik Kelas X IPA - Ellen Tandilangi; Dientje Fintje Pendong; Tika Putri Agustina (Jurnal Cakrawala Pendidikan dan Biologi, 2026)
This study aims to develop an electronic module (e-module) for biology learning that integrates the scientific approach on biodiversity material for tenth-grade science students, as well as to assess the feasibility level and user responses to the developed product. The research method used is Research and Development (R&D) with the 4D development model consisting of four stages: define, design, develop, and disseminate. The study was conducted at SMA Negeri 1 Kawangkoan Barat involving 13 tenth-grade science students and one biology teacher as trial subjects. Data were collected through interviews and questionnaires, then analyzed descriptively using qualitative and quantitative approaches with a Likert scale. The results showed that the developed e-module received a media expert validation score of 92% and a content expert validation score of 95%, both categorized as very feasible. Teacher responses reached 89% and student responses reached 89.61%, also categorized as very feasible. Therefore, the biology e-module based on the scientific approach for biodiversity material is declared feasible and ready to be used as teaching material in tenth-grade science biology learning.